The dynamics of micro-conflicts and uncertainty in successful and unsuccessful design teams. (May 2017) - Paletz, Susannah B.F.; Chan, Joel; Schunn, Christian D.
Abstract : What differentiates successful from unsuccessful design teams? Building on new research on design innovation that emphasizes interactions between social and cognitive processes, we investigated a potential distinguishing feature: Successful design teams may harness interpersonal conflicts (a social design process) to mitigate uncertainty (a cognitive design process). We analyzed temporal relationships between brief, expressed interpersonal disagreements and subsequent spoken individual uncertainty in 30 h of conversations of 10 successful and 11 unsuccessful engineering product design teams. We discovered that micro-conflicts were followed by a relative reduction in uncertainty in successful design teams, whereas uncertainty rose after micro-conflicts in unsuccessful design teams, suggesting that interactions between conflict and uncertainty may be a differentiating factor for design team success. Highlights: Team disagreement can have immediate consequences for uncertainty. These consequences are different for successful and unsuccessful design teams. Uncertainty decreases after conflicts in successful teams. Conversely, uncertainty relatively increases after conflicts in unsuccessful teams.